Enzimas envolvidas na hidrólise de sacarose em folhas e casca e enraizamento de brotações caulinares de seringueira - Nascimento, Marilza Neves do (2010)
The pathways related to the hydrolysis of sucrose are considered the starting point for the biosynthesis of latex and the key enzymes involved in this process are the sucrose synthase (SuSy) and different isoforms of invertases, however, the relative contribution of each of these enzymes in the hexoses production for the metabolism is not known. The production of selected and/or improved clones is another important aspect to the culture of rubber trees beyond simply depending on grafting process, following the example of rooting shoot cuttings, however chemical and/or anatomical characteristics can derail the usage of this method. Thus, this study aimed to characterize the appropriate conditions for in vitro and in vivo tests on the activities of the enzymes involved in the hydrolysis of sucrose (invertases and their isoforms and sucrose synthase) in the leaf and bark, in addition to assess whether chemical components and/or anatomical characteristics of sprouts constitute limitations to rooting of the structures in rubber trees. The plant material used for evaluating the activity of the invertase enzymes (and its isoforms) and sucrose synthase (SuSy) was collected from 5 adult plants of rubber trees from clone RRIM 600 at 22 years of age. The plant material (shoot cuttings) was collected in a clonal garden for the plant material propagation experiment, in which the plants were submitted to pruning to induce new shoots. The results led to the conclusion that in the leaf and bark tissues from rubber trees, the hydrolysis of sucrose was carried out predominantly by the acidic invertases. The appropriate conditions for the enzymatic assays in leaf tissues were: in vivo assay: pH 3.5 for the acidic invertase and 7.5 for the neutral invertase, 200 mM sucrose concentration and temperature of 37 ºC; in vitro assay: pH 3.5 for the acidic invertase and 6.0 for the neutral invertase, 200 mM sucrose concentration and a temperature of 37 ºC. The appropriate conditions for the enzymatic assays in the bark tissue were: in vivo assay: pH 3.5 for the acidic invertase and 6.5 for the neutral invertase, 200 mM sucrose concentration; in vitro assay: pH 4.0 for the acidic invertase and 6.5 for the neutral invertase, 200 mM sucrose concentration and a temperature of 37 ºC. Non-enzymatic hydrolysis of sucrose occurred in the range of pH 2.0-3.5. The asexual propagation by stem cuttings in the rubber tree did not prove to be promising. It was observed that the auxins did not induce the rooting system and that the stem budding showed a continuous perivascular sheath of sclerenchyma after seven weeks of development, possibly acting as an anatomical barrier towards the emergence of the root primordium. The rubber tree latex promoted an inhibitory effect on the rooting process of cassava, when these were subjected to different immersion times.